The gastrointestinal manifestation of constitutional mismatch repair deficiency syndrome: from a single adenoma to polyposis‐like phenotype and early onset cancer. (10th November 2014) - Levi, Z.; Kariv, R.; Barnes‐Kedar, I.; Goldberg, Y.; Half, E.; Morgentern, S.; Eli, B.; Baris, H.N.; Vilkin, A.; Belfer, R.G.; Niv, Y.; Elhasid, R.; et al.
<x xml:space="preserve">Abstract</x> Data on the clinical presentation of constitutional mismatch repair deficiency syndrome (CMMRD) is accumulating. However, as the extraintestinal manifestations are often fatal and occur at early age, data on the systematic evaluation of the gastrointestinal tract is scarce. Here we describe 11 subjects with verified biallelic carriage and who underwent colonoscopy, upper endoscopy and small bowel evaluation. Five subjects were symptomatic and in six subjects the findings were screen detected. Two subjects had colorectal cancer and few adenomatous polyps (19, 20 years), three subjects had polyposis‐like phenotype (13, 14, 16 years), four subjects had few adenomatous polyps (8, 12–14 years) and two subjects had no polyps (both at age 6). Of the three subjects in the polyposis‐like group, two subjects had already developed high‐grade dysplasia or cancer and one subject had atypical juvenile polyps suggesting juvenile polyposis. Three out of the five subjects that underwent repeated exams had significant findings during short interval. The gastrointestinal manifestations of CMMRD are highly dependent upon age of examination and highly variable. The polyps may also resemble juvenile polyposis. Intensive surveillance according to current guidelines is mandatory.